Peculiarities of PED virus pathogenesis in neonatal non-immune piglets on Ukraine farms - Masiuk, D. N.; Nedzvetsky, V. S.; Sosnztskyi, A. I.; Kokariev, A. V.; Zavhorodnii, A. I. (Regulatory Mechanisms in Biosystems, 2018)
The article presents the results of study of the immune and tissue features of pathogenesis of PED virus in neonatal piglets in Ukraine. Clinical and epizootological analysis was performed in three separate agricultural enterprises with adverse epidemiological situation with PED virus. Blood samples and fragments of the small intestine of PEDv infected piglets were used to study the characteristics of the pathogenesis of PED virus. It has been determined that the pathogenesis of super-acute infection by the PED virus in 1–7 day old non-immune piglets proceeds according to the classic type of infectious process with a relay transmission of the pathogen. Moreover, diarrhea syndrome has induced the development of irreversible and lethal pathophysiological lesions by replication the PED virus in enterocytes of infected piglets. Pathogenetic changes observed in PEDv infected piglets were combined with the following components: acute inflammatory-necrotic process in the tissue of the intestine, destruction and desquamation of the epithelium of the small intestine. The infection process on day 3–5 of manifestation of clinical signs of PED virus is accompanied with an increase in the number of erythrocytes, leukocytes and monocytes, hemoglobin, hematocrit level and aminotransferase activity. In addition, PED virus infection induced an increase in IgM levels and the number of phagocytizing leukocytes with increased aggressiveness and digestive power. The duration of the release of PED virus with feces is 26–37 days after cessation of watery diarrhea. The concentration of PEDv in the feces of convalescent piglets ranged from 120 to 1700 equivalent genome in 1 g of tissue. Parasite coenotic associations of the microbiocenosis of the digestive tract of PED virus infected piglets did not have time to form into stable epitopes. There was a constant quantitative prevalence of transient microbiota and a decrease in the share of probiotic microorganisms. The intestinal microflora consists of random transient microbiota of the environment with pathogenic properties. The results presented show evidence that molecular and cell-mediated immunological events in non-immune piglets have the initial stage of the specific progress of immune response against PEDv.